Preliminary study on the development of an antistretch marks water-in-oil cream: ultrasound assessment, texture analysis, and sensory analysis - Bogdan C; Moldovan ML; Man IM; Crișan M (Dove Medical Press, 2016)
Cătălina Bogdan,1 Mirela L Moldovan,1 Ioana Manuela Man,2 Maria Crișan,2 1Department of Dermopharmacy and Cosmetics, Faculty of Pharmacy, 2Department of Histology, Faculty of Medicine, University of Medicine and Pharmacy “Iuliu Hațieganu”, Cluj-Napoca, Romania Purpose: Striae distensae represent the result of the failure of the dermis to sustain intrinsic mechanical forces. Intensive moisturization of the lesions and use of emollient oils have been recommended for the prevention and treatment of striae distensae rubra. The aim of this research was to formulate an emollient water-in-oil cosmetic cream containing argan oil, which may be helpful in the prevention or early treatment of striae distensae. Patients and methods: Sensory evaluation of the consistency, firmness, adhesiveness, oiliness, spreadability, and rapidity of penetration into the skin was evaluated by 22 volunteers using 10-point scales for each descriptor. The instrumental characterization of the cream was performed using Brookfield® CT3 Texture Analyzer. The cutaneous changes induced by the topical use of the cream were evaluated by assessing the thickness of the epidermis, hydration, and elasticity of the skin using DermaLab® Combo scanner. Results: Ultrasound measurements showed an improvement in the elasticity of the epidermis following the application of cream. The product was well tolerated and appreciated by the consumers in terms of its spreadability, penetration ability, and lack of stickiness. The values recorded for texture analysis were firmness 10.16±0.15 mJ, adhesiveness 30.94±6.87 g, consistency 1229.50±119.78 g, spreadability 481.50±39 g, and stringiness 0.56±0.09 mJ. Conclusion: A water-in-oil cream containing argan oil and emollient ingredients with appropriate physical characteristics was obtained. In vivo study of clinical efficacy revealed a positive effect on increasing the skin elasticity, suggesting that the cream may be helpful in the prevention or early treatment of striae distensae. Keywords: striae distensae, cosmetic cream, sensory properties, cream evaluation